Employee experiences in underground workplaces: a qualitative investigation. Issue 11 (1st November 2020) - Venugopal, Vinita; Roberts, Adam Charles; Kwok, Kian-Woon; Christopoulos, George I.; Soh, Chee-Kiong
Abstract: Underground workplaces (UWS) are increasingly being recognised as a sustainable solution to concerns regarding lack of space facing megacities. UWS can multiply available space by reducing urban sprawl thereby improving quality of life in cities. However, developing workplaces that respond to the needs and preferences of occupants will be a crucial factor in determining the success of this concept. We examine the experiences of existing full-time employees of a large underground facility in North America and analyse how these are related to company policies and other organisational factors. From in-depth interviews of 73 participants, three predominant themes emerged from the analyses: environmental effects (e.g. lack of sunlight), design (e.g. the unique working environment), and organisational factors and social dynamics (e.g. policies regarding breaks). We discuss these themes in relation with interventions that may improve employee comfort and retention and suggest that many factors are within organisational control. Practitioner Summary: Underground workplaces are a sustainable solution to lack of urban space. However, developing effective workplaces is crucial to their success. We examine the experiences of existing employees of an underground facility in North America. We suggest that most negative attitudes towards underground spaces can be mitigated through simple organisational interventions. Abbreviations: UWS: underground workplaces; IRB: institutional review board